Psychological Dynamics of Adolescents with Conduct Disorder: A Case Study Using Skinner’s ABC Model - Sufiana Khadijah; Qurrota Ayuni Fitriana (International Conference on Psychology and Education (ICPE), 2025)
Conduct disorder focuses on an individual’s inability to control behavior that harms the rights of others or violates applicable social norms. This study aimed to explore and understand the psychological dynamics in individuals with behavioral disorders. The researcher used a qualitative method with a case study approach to reveal patterns of stimulus, response, and consequence based on Skinner’s ABC model. Data collection techniques were conducted through in-depth interviews with a 13-year-old subject and significant others, direct observation, and medical record review. The results showed that the subject exhibited chronic truant behavior for the past six months, physical and verbal aggression toward the mother, and impulsivity in decision making. Excessive interest in bantengan activities is the main trigger for the emergence of maladaptive behavior, which is then reinforced by consequences in the form of instant gratification and lack of control and sanctions from the environment.